YEATS’S CELTIC HELIOLATRY AND/OR ELITISM - Dicu, Maria Camelia (European Scientific Journal, ESJ, 2013)
The present article intends to explore a delicate subject matter: whether or not the Anglo-Irish poet, W. B. Yeats’s political orientation was of fascist origin indeed or it was only a matter of choice in point of poetical creation under his views on world and life and his elitist opinions. Therefore, in the first part, the article aims at examining Michael North’s study with view to demonstrate that Yeats’s poems and, in fact, his entire literary creation were a matter of search for the “unity of being” and the “perfect poetic expression”, which he had never ceased to look for along his life time. The second part of the article aims at demonstrating that his poem “The Second Coming”, which launched the contradictory opinions regarding Yeats’s political orientation, was nothing more than the poet’s conclusions comprised also in A Vision and which was not only his opinion, but it inscribed in a row of similar opinions pertaining to philosophers of the moment regarding the cycles of life on earth.